Rol' navyka psichoemocional'noj samoreguljacii v processe adaptacii sportsmenov k uslovijam smeny casovych pojasov - Kozlovskij, A. P.; Kalinkin, L. A.; Morozov, V. N.; Skomorochov, A. A.; Eršov, V. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The paper presents the results of the analysis of the experimental data obtained in the pre-stage training elite athletes on sailing. The main task was to evaluate the role of the formation of the athletes of the skill of emotional self-regulation based on the method of biofeedback (biofeedback training) in the process of adapting to the factor of change of 6 time zones. It is established that fast, within less than a day movement in a new time zone differing from habitual conditions for 6 hours leads to violation of psychophysiological functions. It is also determined that the process of adaptation with the gradual normalization of the functional state of the organism proceeded more effectively in athletes trained to develop the skill of psycho-emotional self-regulation.